A Multifactorial Approach to Overuse Running Injuries: A 1-Year Prospective Study. (May 2020) - Winter, Sara C.; Gordon, Susan; Brice, Sara M.; Lindsay, Daniel; Barrs, Sue
Background: Because of the complex and multifaceted nature of running injuries, a multifactorial approach when investigating running injuries is required. Hypothesis: Compared with uninjured runners, injured runners would exhibit different running biomechanics, display more fatigue changes, and would run a greater weekly running volume; more injured runners would also report having a previous injury. Study Design: Prospective cohort study. Level of Evidence: Level 4. Methods: At commencement of the study, data were collected on demographics, anthropometrics, training history, previous injury history, and center-of-mass accelerations during a long-distance overground run. Participants completed weekly training diaries and were monitored for 1 year for an injury. Results: A total of 76 runners completed the study, with 39 (22 male; 17 female) reporting an injury. Compared with male uninjured runners, male injured runners were heavier and ran a greater weekly distance. Male runners (injured and uninjured) exhibited increases in mediolateral center-of-mass accelerations during the run. Compared with female uninjured runners, female injured runners were heavier, ran with longer flight times and lower step frequencies, and more of them had reported an injury in the previous year and had increased speed training in the weeks prior to injury. Over 60% of male injured runners and over 50% of female injured runners had increased their weekly running distance by >30% between consecutive weeks at least once in the 4 weeks prior to injury. Conclusion: Factors that may be related to injury for male runners include being heavier, running a greater weekly distance, and exhibiting fatigue changes in mediolateral center-of-mass accelerations. Factors that may be related to injury for female runners include being heavier, having an injury in the previous year, running with longer flight times and lower step frequencies, and increasing speed training prior to injury. Increases in weekly running distance in 1 consecutive week (particularly >30%) needs to be monitored in training, and this along with the other factors found may have contributed to injury development. Clinical Relevance: This study found that multiple factors are related to running injuries and that some factors are sex specific. The findings can aid in injury prevention and management.